Study behavior promotion in children - Results of an educational program for parents and guardians (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
Parents or guardians frequently do not have the necessary repertoires to promote effective self-study behavior on their children. This program had, as a goal, to carry out and assess an educational program for parents or guardians of children with a history of low school performance. Three guardians participated in the research. They were selected by teachers because their children presented learning difficulties. Measures of pre-test, training and post-test were collected through interviews with the guardians and children. In addition, activities were performed in eight meetings, the parents received a handout with the most relevant information; every two session they passed through an evaluation. The results indicate that the program may have promoted changes in the repertoire of parents/guardians to deal with the studies of children and/or on the daily interaction routine in the family environment, especially for one of the three participants
Keywords: parents training; study behavior; school failure; educational program